A New Single-Step PCR Assay for the Detection of the Zoonotic Malaria Parasite Plasmodium knowlesi - Lucchi, Naomi W.; Poorak, Mitra; Oberstaller, Jenna; DeBarry, Jeremy; Srinivasamoorthy, Ganesh; Goldman, Ira; Xayavong, Maniphet; da Silva, Alexandre J.; Peterson, David S.; Barnwell, John W.; Kissinger, Jessica; Udhayakumar, Venkatachalam (PLOS ONE, 2012)
Background Recent studies in Southeast Asia have demonstrated substantial zoonotic transmission of Plasmodium knowlesi to humans. Microscopically, P. knowlesi exhibits several stage-dependent morphological similarities to P. malariae and P. falciparum. These similarities often lead to misdiagnosis of P. knowlesi as either P. malariae or P. falciparum and PCR-based molecular diagnostic tests are required to accurately detect P. knowlesi in humans. The most commonly used PCR test has been found to give false positive results, especially with a proportion of P. vivax isolates. To address the need for more sensitive and specific diagnostic tests for the accurate diagnosis of P. knowlesi, we report development of a new single-step PCR assay that uses novel genomic targets to accurately detect this infection. Methodology and Significant Findings We have developed a bioinformatics approach to search the available malaria parasite genome database for the identification of suitable DNA sequences relevant for molecular diagnostic tests. Using this approach, we have identified multi-copy DNA sequences distributed in the P. knowlesi genome. We designed and tested several novel primers specific to new target sequences in a single-tube, non-nested PCR assay and identified one set of primers that accurately detects P. knowlesi. We show that this primer set has 100% specificity for the detection of P. knowlesi using three different strains (Nuri, H, and Hackeri), and one human case of malaria caused by P. knowlesi. This test did not show cross reactivity with any of the four human malaria parasite species including 11 different strains of P. vivax as well as 5 additional species of simian malaria parasites. Conclusions The new PCR assay based on novel P. knowlesi genomic sequence targets was able to accurately detect P. knowlesi. Additional laboratory and field-based testing of this assay will be necessary to further validate its utility for clinical diagnosis of P. knowlesi.